Evaluasi Keberlanjutan Lumbung Pangan Masyarakat Dalam Mendukung Ketahanan Dan Swasembada Pangan Nasional Di Kabupaten Pidie - Hasballah, Julia; Karnilawati, Karnilawati; Safrika, Safrika; Khalidin, Khalidin (Jurnal Sosial Ekonomi Pertanian, 2025)
Community Food Barns (Lumbung Pangan Masyarakat or LPM) serve as a vital instrument in maintaining national food reserve stability; however, multidimensional evaluations of their sustainability are often overlooked. This study aims to evaluate the sustainability status and development strategies of LPM in Pidie Regency, Aceh. The unit of analysis involved 150 LPM member farmers selected via simple random sampling. A Multi-Dimensional Scaling (MDS) approach using Rapfish was employed to assess sustainability ordination across ecological, economic, and social dimension indicators. The analysis indicates that LPM falls under the "moderately sustainable" category in aggregate. Social and ecological dimensions dominate, whereas the economic dimension exhibits the lowest index (54.03–57.20%). Key leverage factors include land quality, market access, and compliance with environmental regulations. This study contributes theoretically by adapting the MDS model to measure the resilience of agrarian community-based food institutions. Practical implications emphasize the necessity of economic business diversification and managerial strengthening to ensure adaptive regional food self-sufficiency.